Case Report Rare presentation of CNS manifestation of pseudo inflammatory tumor which responded to steroid: Rare presentation of CNS manifestation of pseudo inflammatory tumor (Bombay Hospital Journal, 2026)
Abstract: Aim- Rare presentation of CNS manifestation of pseudo inflammatory tumor which responded to steroid.Background- Inflammatory pseudotumor are rare, benign, tumor-like lesions characterized by chronic inflammatory cell infiltration, which can mimic malignant tumors both clinically and radiologically.Case Description- Here, we present a case of a patient diagnosed with an inflammatory pseudotumor involving the left 7th and 8th cranial nerves, who presented with symptoms of severe headache, recurrent vomiting, dizziness, and gait ataxia. Initial examination revealed no fever or other systemic symptoms, and MRI imaging showed enhancement along the left 7th and 8th nerve complex.Conclusion-Elevated serum IgG4 levels supported an inflammatory etiology, while cerebrospinal fluid (CSF) analysis and other tests ruled out infection or malignancy. The patient showed significant improvement in symptoms after corticosteroid therapy with IV dexamethasone and supportive careClinical Significance-This case highlights the diagnostic challenge posed by inflammatory pseudotumor in cranial nerves and underscores the importance of distinguishing them from other lesions to guide appropriate treatment.
Keywords: IgG4; 7th and 8th nerve involvement; benign lesion; MRI skull base